Osteopontin-Enhanced Autophagy Attenuates Early Brain Injury via FAK–ERK Pathway and Improves Long-Term Outcome after Subarachnoid Hemorrhage in Rats - Chengmei Sun; Budbazar Enkhjargal; Cesar Reis; Tongyu Zhang; Qiquan Zhu; Keren Zhou; Zhiyi Xie; Lingyun Wu; Jiping Tang; Xiaodan Jiang; John H. Zhang (Cells, 2019)
Osteopontin (OPN) enhances autophagy, reduces apoptosis, and attenuates early brain injury (EBI) after a subarachnoid hemorrhage (SAH). A total of 87 Sprague−Dawley rats were subjected to sham or SAH operations to further investigate the signaling pathway involved in osteopontin-enhanced autophagy during EBI, and the potential effect of recombinant OPN (rOPN) administration to improve long-term outcomes after SAH. Rats were randomly divided into five groups: Sham, SAH + Vehicle (PBS, phosphate-buffered saline), SAH + rOPN (5 μg/rat recombinant OPN), SAH + rOPN + Fib-14 (30 mg/kg of focal adhesion kinase (FAK) inhibitor-14), and SAH + rOPN + DMSO (dimethyl sulfoxide). Short-term and long-term neurobehavior tests were performed, followed by a collection of brain samples for assessment of autophagy markers in neurons, pathway proteins expression, and delayed hippocampal injury. Western blot, double immunofluorescence staining, Nissl staining, and Fluoro-Jade C staining assay were used. Results showed that rOPN administration increased autophagy in neurons and improved neurobehavior in a rat model of SAH. With the administration of FAK inhibitor-14 (Fib-14), neurobehavioral improvement and autophagy enhancement induced by rOPN were abolished, and there were consistent changes in the phosphorylation level of ERK1/2. In addition, early administration of rOPN in rat SAH models improved long-term neurobehavior results, possibly by alleviating hippocampal injury. These results suggest that FAK−ERK signaling may be involved in OPN-enhanced autophagy in the EBI phase after SAH. Early administration of rOPN may be a preventive and therapeutic strategy against delayed brain injury after SAH.